Evaluación de calidad de servicio y su influencia en la satisfacción del cliente en el comercial Malecón 2000 de la ciudad de Tosagua - Conforme Ponce, Samantha Andreina (2022)
The investigation was carried out in the commercial company "Malecón 2000" dedicated to the purchase and sale of mass consumption in the Tosagua canton, in which the influence of the quality of service on customer satisfaction was evaluated and diagnosed, said process was developed through three phases: identify the level of service quality, determine the influence of service quality and its relationship with customer satisfaction in the commercial and propose an action plan, to find relevant results, inductive methods were used. , deductive, analytical, descriptive, statistical and correlational Rho of Spearman that as a whole contributed to the systematization of the procedure, likewise, techniques such as the survey, the Ishikawa and dispersion diagram were used, which showed the type of analogy existing in the In addition, instruments such as the questionnaire and the servqual method were used. This methodology generated the following results: the survey was addressed to 380 commercial, in the application of the instrument a good level of satisfaction is found, therefore when applying the quality index revealed a small gap between the expectations and perceptions of -0.62, in addition, a significant correlation between the dependent and independent variable of 0.984 was shown, being this directly proportional, later, the results were reflected in the stratified Ishikawa diagram to determine the causes and their effects, and finally, alternatives were proposed to improve the company's performance.